อินเดีย : ตลาดที่มีศักยภาพสำหรับผู้ประกอบการไทย - โชคสุชาติ ธิดารัตน์ (RMUTP Research Journal Sciences and Technology, 2012)
บทคัดย่อ อินเดียมีการเจริญเติบโตทางเศรษฐกิจและการพัฒนาในช่วง 2 ทศวรรษที่ผ่านมา จากการประเมินศักยภาพด้วยกรอบสภาพแวดล้อมด้านต่าง ๆ สรุปได้ว่า จุดแข็ง ได้แก่ (1) เป็นประเทศประชาธิปไตยเสรี (2) มีความสมบูรณ์ของทรัพยากร (3) มีการเจริญเติบโตอย่างต่อเนื่อง (4) กำลังซื้อเพิ่มขึ้น (5) มีอุตสาหกรรมซอฟต์แวร์ระดับโลก จุดอ่อน ได้แก่ (1) การกระจายรายได้ไม่สมดุล (2) สาธารณูปโภคยังไม่ได้รับการพัฒนา(3) พิธีการศุลกากรยุ่งยาก โอกาส คือ (1) เป็นตลาดใหญ่ (2) เป็นตลาดที่ดีของธุรกิจก่อสร้าง (3) สังคมทันสมัย(4) มี FTA ไทย-อินเดีย ส่วนอุปสรรค ได้แก่ (1) มีการกีดกันทางการค้า (2) การขนส่งไม่พัฒนา (3) มีการเลียนแบบสินค้า ดังนั้น ผู้ประกอบการไทยควรเตรียมความพร้อมอย่างดี เช่น การศึกษาตลาดอินเดีย กฎระเบียบทางธุรกิจ เป็นต้น นอกจากนี้ ภาครัฐและเอกชนควรเข้ามาสนับสนุนด้วยเพราะจะทำให้ผู้ประกอบการระมัดระวังการทำธุรกิจในอินเดีย คำสำคัญ : อินเดีย; ตลาดที่มีศักยภาพ; ผู้ประกอบการไทย Abstract During the last two decades, India has made significant strides in its economic growthand development. According to the assessment of potential by the comparative environmentalframeworks, the strengths are summarized as follows: (1) being a democratic country, (2) havingplentiful resources, (3) enjoying consecutive high economic growth, (4) having increasedpurchasing power and (5) having the world class of software industries. Weaknesses are asfollows: (1) unbalanced income distribution, (2) undeveloped infrastructures and (3) havingintricate process of custom. Opportunities are as follows: (1) huge market, (2) good market ofinfrastructure businesses, (3) more contemporary society and (4) the existing Thai–India FTA.Threats are as follows: (1) having trade barriers, (2) undeveloped transportation and (3) havingimitation of goods. Therefore, Thai entrepreneurs should get themselves well-prepared. Thefollowings are examples of what potential investors should consider researching: India’s marketstudy, the regulation study of business and etc. The government and private sectors should helpequip the entrepreneurs with whatever necessary to make them well-prepared. After all, the roleof the government and private sectors is indispensable to their success. Keywords : India; The Potential Market; Thai Entrepreneurs